Global and non Global Solutions for Some Fractional Heat Equations With Pure Power Nonlinearity. (1st August 2017) - Saanouni, Tarek
Abstract: The initial value problem for a semi-linear fractional heat equation is investigated. In the focusing case, global well-posedness and exponential decay are obtained. In the focusing sign, global and non global existence of solutions are discussed via the potential well method.